Validity of learning website of kapita selekta mathematics course at UIN Suska Riau Students - Thahir, Musa; Roza, Yenita; Murni, Atma (Malikussaleh Journal of Mathematics Learning (MJML), 2018)
This article is based on the limited lecture model for Kapita Selekta Mathematics (KSM) courses.Â  This article aims to reveal the results of technology validation of the website of the mathematics proficiency course (KSM) on UIN Suska Riau students. This article uses a development research model that uses Sugiyono's research steps but only limited to two stages, namely design stage and product validation stage. The validated aspect of the learning website is graphic feasibility and program feasibility with indicators: 1) the size of the learning website, 2) the design of the learning website, and 3) the design of the content of the learning website. The validation instrument is a questionnaire using Likert scale that is filled by three expert technology experts. Assessment of the validity of the learning web on the aspect of feasibility of the graphics resulted in a total validity value of 3.9 with valid categories. As for the web learning on the feasibility aspect of the program to produce the value of validity as a whole that is 4 with valid categories